Implementation and Preliminary Evaluation of a 12-Week Cognitive Behavioural and Motivational Enhancement Group Therapy for Cannabis Use Disorder - Leanne Trick; Kevin Butler; Zoe Bourgault; Julianne Vandervoort; Bernard Le Foll (SAGE Publishing, 2023)
Background: The purpose of this paper is to provide a preliminary evaluation of treatment outcomes, retention and client satisfaction following a 12-week combined cognitive behavioural therapy (CBT) and motivational enhancement therapy (MET) group treatment for cannabis use disorder (CUD) delivered in an outpatient setting. Implementation of the program is also described. Methods: A retrospective observational cohort study was conducted using data collected from medical records and self-report assessments. Participants were treatment-seeking cannabis users at the Centre for Addiction and Mental Health, Toronto. Cannabis use, cannabis-related problems, craving, withdrawal symptoms, self-efficacy for remaining abstinent, depression and anxiety were assessed pre- and post-treatment. Treatment retention was calculated by inspecting clinic attendance records, and client satisfaction was evaluated using an anonymous feedback survey. Potential predictors of treatment outcomes and retention were investigated in exploratory analyses. Results: Cannabis use was lower and days of abstinence higher post-treatment (vs pre-treatment). Post-treatment improvements in cannabis-related problems, craving, withdrawal symptoms, self-efficacy and mood were also observed. Completion of group treatment (⩾75% of sessions attended) was 57% and moderate levels of treatment satisfaction were reported. Conclusions: This study provides preliminary evidence that a 12-week combined CBT and MET treatment for cannabis use disorder delivered in a novel group setting improves cannabis use outcomes. Potential predictors of reduced cannabis use and retention were identified. Future controlled studies are warranted, and strategies for increasing retention should be explored.